Cyclodextrin neoglycoconjugates - Carmen Ortiz Mellet; Jacques Defaye; José M. Garcia Fernández (ՀՀ ԳԱԱ հրատ.)
Progress towards the use of cyclodextrins as drug targetting devices is summarized.
Keywords: Biology; Biochemistry